2022
DOI: 10.1021/acs.energyfuels.2c02011
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo and Sensitivity Analysis Methods for Kinetic Parameters Optimization: Application to Heavy Oil Slurry-Phase Hydrocracking

Abstract: A methodology to estimate kinetic parameters using the Monte Carlo algorithm and sensitivity analysis is described. The approach is applied to the experimental data reported in the literature for slurry-phase hydrocracking of heavy oil with ionic liquids. All experiments were carried out in a batch reactor at a reaction temperature of 430 °C, H 2 pressure of 12.3 MPa, and reaction times of 0.5−6 h. It is demonstrated that the reported values of kinetic parameters can be optimized so that the average absolute e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The objective function was the average absolute error (AAE) because it has shown better results by distributing the error equally to all the fractions involved. 7,14 To compare with the results obtained by Tang et al, 23 the sum of square error (SSE) and the determination coefficient (R…”
Section: Parameter Estimationmentioning
confidence: 97%
See 2 more Smart Citations
“…The objective function was the average absolute error (AAE) because it has shown better results by distributing the error equally to all the fractions involved. 7,14 To compare with the results obtained by Tang et al, 23 the sum of square error (SSE) and the determination coefficient (R…”
Section: Parameter Estimationmentioning
confidence: 97%
“…The methodology for the estimation of the reaction rate coefficients involves the following steps: 7,14,21,24 the initial values for the optimization step are obtained using the reported literature values and the Monte Carlo algorithm, which is based on the use of random numbers (in a range of 1 × 10 1 to 1 × 10 −8 ) for each kinetic parameter. It has been previously demonstrated that using initial values determined with the Monte Carlo algorithm, better results are achieved than using other initial values (Figure S5).…”
Section: Parameter Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the manner to represent the kinetic modeling and estimate the kinetic parameters of reactions is through ordinary/partial differential equations that are solved by numerical methods and linear/nonlinear optimization techniques, it is crucial to discuss some of the most popular and useful methods used worldwide to carry out parameter estimations, as well as their advantages and disadvantages. , …”
Section: Perspectives In Kinetic Modeling For Ulsd Productionmentioning
confidence: 99%
“…Since the manner to represent the kinetic modeling and estimate the kinetic parameters of reactions is through ordinary/partial differential equations that are solved by numerical methods and linear/nonlinear optimization techniques, it is crucial to discuss some of the most popular and useful methods used worldwide to carry out parameter estimations, as well as their advantages and disadvantages. 96,97 Alcaźar and Ancheyta 98 proposed a methodology based on sensitivity analysis to estimate the kinetic parameters of heterogeneous kinetic models. This methodology consists of three main steps: initialization of parameters (with the Monte Carlo method), nonlinear optimization (using the Levenberg− Marquardt algorithm), and sensitivity analysis.…”
Section: Perspectives In Kinetic Modeling For Ulsd Productionmentioning
confidence: 99%